Bandish as text: re-reading Khayal compositions by Sadarang and Adarang - Khasnobis, Barnashree (Routledge, 2024)
This book provides a socio-cultural analysis of khayal bandishes composed by Nemat Khan Sadarang and Feroze Khan Adarang'